Numerical simulation and design of stainless steel columns under fire conditions - Martins, André Dias; Gonçalves, Rodrigo; Camotim, Dinar (Engineering structures, 2021)
•Post-buckling behaviour of stainless steel columns under fire conditions studied.•Finite element models developed to obtain the response of columns exposed to fire.•Sizable failure load data for duplex/ferritic/austenitic stainless steel columns.•Influence of temperature on residual stresses of stainless steel columns studied.•Evaluation of the current European and recently proposed design rules for columns. This paper presents and discusses results of an ongoing numerical investigation on stainless steel columns under elevated temperatures and prone to local or global buckling, performed in the context of the project “StaSteFi – Fire Design of Stainless Steel Members”. Geometrically and materially non-linear shell finite element models are employed to obtain the structural response and the failure loads of columns (i) with several cross-section shapes (SHS, RHS, CHS, EHS and I-section), (ii) prone to local or global (major- and/or minor flexural) buckling, (iii) made from three common stainless steel grades (ferritic 1.4003, austenitic 1.4301 and duplex 1.4462), (iv) subjected to various elevated temperatures (θ = 100, 200, 300, 400, 500, 600, 700 and 800 °C), (v) containing both initial geometrical imperfections and residual stresses, and (vi) covering a wide local or global slenderness range. The variation of the influence of the residual stresses as the temperature increases is also assessed. Lastly, the failure loads gathered are used to assess the quality of their prediction provided by (i) the currently codified Eurocode 3 stainless steel fire design rules, and (ii) recently proposed design rules for local and global (flexural) failures of I-section stainless steel columns, as well as to explore their extension/accuracy in the context of SHS and RHS columns.